Workshop Pemanfaatan Teknologi Untuk Mengefektifkan Proses Pembelajaran dan Administrasi Di Sekolah - SRI WULANDARI; Wahyuhana, Ratika Tulus (Jurnal ABDI RAKYAT, 2024)
In the digital era, technology integration is an urgent need to support academic and administrative activities in schools. This workshop aims to increase the effectiveness of the learning and administration process at Karanglincak Elementary School, Kragan District, Rembang Regency, through the use of technology. The methods used in the workshop include practical training sessions, interactive discussions, and simulations of using relevant software. The main focus of this activity is on the use of Google applications for use in managing student data, creating materials and digital learning. The expected results of this activity include increasing the technological competence of educators, efficiency in managing school administration, and creating a more interesting and effective learning experience for students. With the implementation of appropriate technology, it is hoped that Karanglincak Elementary School can become a school model that is adaptive to current developments, supporting the sustainability of quality education in rural areas.